Refleksi Feminisme dalam Novel The Great Gatsby Karya F. Scott Fitzgerald - Ahmad Ridwan (Indonesian Journal of Applied Linguistics Review, 2022)
The purpose of this study was to describe the reflection of feminism and the factors causing the rebellion emergence on female characters in this novel The Great Gatsby written by Francis Scott Key Fitzgerald. The research method used was descriptive method with the qualitative research form. The approach used was a feminist literary criticism approach. The technique used was documentary study. The data source was a novel The Great Gatsby (1925) using his background in New York. The problem of this research was how the feminism reflection was emphasized on the figure of women like Daisy, Jordan and Myrtle, who were female figures in the novel The Great Gatsby, especially their behavior towards men. The results showed another side of women's lives, a phenomenon that rarely occured when a woman's determination and determination tried to get out of a life that was not taking its side. The position of women implied the perception of society that the position of women, especially with regard to work was still underestimated